A Study of the Correlation of Renewable Energy Consumption in Egypt with Specific Economic and Environmental Indicators - Fahmy, Marwa Salah ElDin; Gareeb, Mona Mohamed (The Arab Journal of Administration, 2025)
The research problem is to measure the extent to which renewable energy (hydroelectric, solar, wind) consumption in Egypt is correlated with a set of economic indicators that include: GDP, average annual per capita income, unemployment rate, and inflation rate. In addition to these indicators, the correlation between consumption of renewable energy and carbon (CO2) emissions will be studied because of its impact on all economic activities. The study period is between 2000 to 2019. The two years 2020 and 2021 are excluded because of the effect of COVID19 on the economy. Pearson’s correlation coefficient is used to quantize the relation between two sets of data. The first set is the consumption values of renewable energy in Egypt. The second set is the values of the economic indicators mentioned before as well as CO2 emission. Given the different nature of the two sets of data in terms of the units used in the measurement, the standard values of the data will be used so that the correlation between them can be studied. The study shows a moderate direct correlation between the consumption of renewable energy on the one hand and the GDP and the average annual per capita income on the other. There is a weak inverse correlation between the consumption of renewable energy and the unemployment rate, and there is a weak direct correlation between the consumption of renewable energy and the inflation rate for the period. Finally, there is a weak inverse correlation between the consumption of renewable energy and the amount of CO2emissions.